KONFLIK ACEH: STUDI PEMAAFAN PADA AKTIVIS PEREMPUAN ACEH - Khairul Fahmi (PSGA LP2M IAIN Pontianak, 2021)
This study aims to reveal aspects of forgiveness by women activists in the Aceh conflict. This study uses a life story approach in which the data obtained comes from interviews with several Aceh women activists. The results of this study indicate that forgiveness by Aceh women activists is conditional forgiveness. Conditional forgiveness is influenced by religious values, the suffering of victims of conflict in the past, and the issue of the rights of victims during the conflict that have still not been fulfilled.